Preparation of polypropylene composites with high levels of coir short fiber for use in products by injection - Passatore, Claudio Roberto; Leão, Alcides Lopes [UNESP]; Dos Santos Rosa, Derval (Trans Tech Publications, 2016)
The main objective of this investigation was to study the properties of composites of polypropylene (PP) containing different proportions (20, 40 and 60% wt%) of coir short fiber (natural vegetable fiber) without treatment of fibers, for use in products by injection with applications in the automotive industries, construction and other segments. Samples were prepared in a only stage using a high intensity thermokinetic mixer (K-Mixer). Additives were used in the mass fraction of 3 wt% compatibilizer (PP-g-MA), 2.2 wt% processing additive and 0.12 wt% thermal antioxidant. The composites were characterized by tensile test according to ASTM D638- 10. The surface properties of the polymeric matrix with additives were studied by determining the contact angle (CA) in a sessile drop tensiometer and the carbonyl index (CI) by Fourier-transform infrared spectroscopy (FTIR). Thermal properties of the PP and the composition were evaluated by thermogravimetric test, and the interface of the fiber and the matrix in the composites were evaluated using images from scanning electron microscopy (SEM). The CA analysis showed that the PP matrix with additives has become less hydrophobic and the FTIR and the CI that there was a better stabilization of the PP with additives. There was an increase in thermal stability of the composites for all fiber content, which was up to 15 °C above PP for coir fiber composites. In the Young's modulus values showed that the inclusion of fibers reinforced the polymeric matrix and increased the stiffness of the composites, especially in composites containing 60% (wt%) in which the values were ~1.7 times greater than the polypropylene. Images of micrographs showed the interaction of the fiber in the matrix and that despite the hydrophilic character of the fibers and hydrophobic character of the PP, the composites showed non-homogeneous interfaces. These findings confirm the feasibility of using high level of coir fiber in polypropylene composites even without pretreatment of the fibers and the preparation of samples by injection.
Keywords: Coir; Composites; Fibers; Polypropylene